2014
DOI: 10.1182/blood.v124.21.5958.5958
|View full text |Cite
|
Sign up to set email alerts
|

Initial Analysis of Lipid Metabolomic Profile Reveals Differential Expression Features in Myeloid Malignancies

Abstract: Introduction: Lipids are molecules that stand out among the different cellular metabolites by their enormous molecular diversity. Their functions were initially related to the composition of biological membranes and energy storage, but currently, these molecules have been analyzed considering different functions and regulatory signaling (Loizides-Mangold, 2013). It is known that lipid membranes and lipid mediators constitute specific phenotypes, including tumors (Hilvo et al, 2011). Lipid metabolism in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…With the development of mass spectrometry, the lipidomic analysis of peripheral blood was used to investigate the role of lipid on the pathophysiology of hematological diseases. In 2014, Adriana et al reported discriminative lipid pro les in patients with AML, MDS, and myeloproliferative neoplasms using untargeted shotgun LC-MS/MS analyses (3). Although studies on AML and MDS have illustrated the inner correlations of the two entities to some extent, very few studies have focused on the lipid pro les of patients with AA, let alone the comparison of the changes after CsA treatment and the difference between AA and h-MDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of mass spectrometry, the lipidomic analysis of peripheral blood was used to investigate the role of lipid on the pathophysiology of hematological diseases. In 2014, Adriana et al reported discriminative lipid pro les in patients with AML, MDS, and myeloproliferative neoplasms using untargeted shotgun LC-MS/MS analyses (3). Although studies on AML and MDS have illustrated the inner correlations of the two entities to some extent, very few studies have focused on the lipid pro les of patients with AA, let alone the comparison of the changes after CsA treatment and the difference between AA and h-MDS.…”
Section: Discussionmentioning
confidence: 99%
“…It had been used in the early diagnosis, progression and treatment for cancer and other diseases. With regard to hematological diseases, the lipid metabolomic pro le was found to be different in the different myeloid diseases (3). Studies found that the serum sphingomyelin species containing saturated odd chain fatty acids (OCFAs) in the side chain were lower in leukemia and MDS patients compared to normal serum.…”
Section: Introductionmentioning
confidence: 99%
“…A serum lipidomic study on patients with acute myeloid leukaemia and myelodysplastic syndromes showed that the levels of lysomonomethyl glycerophosphocholine could effectively distinguish these patients from healthy controls. 4 A study of the serum lipidome in patients with multiple myeloma demonstrated that serum arachidonic acid levels diminished significantly in patients with monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma (MM) compared with healthy controls. Supplementation with arachidonic acid by injection in MM mice could induce ferroptosis of MM cells, indicating a new drug target for MM.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic studies can facilitate biomarker discovery, diagnosis of disease, and toxic effect assessment of drugs, toxins, and food additives. Considerable interest is focused on small-molecule metabolites (<1500 Da) such as amino acids, ,, lipids, and fatty acids. , Once useful health markers are known, batch-processed, spot analyses are an attractive approach to routine assays. Analyzing blood-derived samples, such as serum, is of primary interest for metabolite assays, but a high concentration of proteins, as well as other biomolecules, usually generates interferences in the following detection step, so sample preparation is required.…”
mentioning
confidence: 99%